In Vitro Evaluation of the Anti-Diabetic Potential of Oxovanadium(IV) Complex with Terpyridine Ligand - Fakhrotun Nisa; Djulia Onggo (Universitas Pendidikan Mandalika, 2026)
An oxovanadium(IV) complex with 2,2′:6′,2″-terpyridine ligand, [VO(terpy)]SO₄, was synthesized and characterized to evaluate its anti-diabetic potential. The complex was synthesized via a direct reaction between VOSO₄ as the metal source and terpyridine ligand in solution and confirmed through conductometric and mass spectrometric analyses. Conductivity measurements indicated that the complex behaves as a 2:2 electrolyte in aqueous solution, dissociating into [VO(terpy)]²⁺ and SO₄²⁻ ions. Mass spectrometry revealed a peak at m/z 150.0098 corresponding to the cationic species. The anti-diabetic activity was evaluated through in vivo studies using alloxan-induced diabetic rats, demonstrating a significant reduction in fasting blood glucose levels. These findings suggest that the oxovanadium(IV)–terpyridine complex is a candidate for further development as an anti-diabetic agent.